The analytic expressions of sensitivity parameters for fiber-optic refiective system - Vytautas Kleiza; Jonas Verkelis (Lietuvos Matematikos Rinkinys)
In this work the analytic expressions of absolute maxima and envelope for family of signals curves have found, which are more accurate than experimental data.